Estudo do potencial de aproveitamento da iluminação natural em escolas municipais de João Pessoa PB - Oliveira, Gimaoli Cavalcanti de (2012)
The built environment must be adapted to the climate in which it is inserted to minimize the environmental impact caused by the unbridled consumption of natural resources. The development of new technologies capable of assessing natural lighting can assist in project directed to the use of energy efficient lighting in architecture. Grounded in the literature review related to these new technologies, this study aimed to analyze the potential use of natural light in the classrooms of municipal schools in the city of João Pessoa. The sample represents a number of schools constructed under the standard design adopted in recent managements of the City of João Pessoa, and still in use. The methodology consisted in situ measurements and computer simulations did using the software Daysim. The results showed that there is great potential for use of daylighting, however, there is a need to implement actions to control glare. The existence of 10 schools constructed under the same project in different sites, allowed us to analyze the degree of influence surrounding the availability of natural light into the classrooms.